Neotypification of Aira setacea Hudson (Poaceae) - Chiapella, Jorge Oscar (2009)
Deschampsia setacea (Hudson) Hackel is a slender grass described originally as Aira setacea Hudson on a plant collected in Stratton Strawless (Norfolk) in the first edition of the Flora Anglica. It has never been typified, and since the herbarium of Hudson has been lost to fire, a neotype is chosen in order to preserve the current application of the name.